SOluble and insoluble immune complex-platelet interactions in rheumatoid inflammation. Issue 5 (October 1978) - Yeatts, R P; Turner, R; Collins, R; Kaufmann, J; Mashburn, H
Abstract : The interactions of soluble and insoluble immunoglobulin G (IgG) complexes with macromolecular rheumatoid factor (RF) and platelets were examined in an in vitro system permitting observation of platelet activities which may contribute to rheumatoid inflammation. Studies of the aggregation phenomenon by the nephalometric technique and by selective sedimentation of 51Cr-labelled platelets revealed no aggregation by platelets exposed to heat aggregated IgG (HAIgG) complexes or their RF precipitates in a plasma test system. Release of serotonin was demonstrated by the increasing radioactivity of platelet supernates to 45 min by 14C-serotonin labelled platelets exposed to insoluble IgG heat aggregates. Significantly less release was shown with saline, native IgG, and soluble IgG complexes. When RF was added to soluble HAIgG complexes, the resulting precipitate caused significantly higher release than controls. No concomitant release of the lysosomal enzyme beta-glucuronidase was detected. Thus, although soluble complexes do not cause significant release of biologically active amines, conversion of soluble complexes to insoluble immune precipitates by RF is associated with this activity which is independent of platelet aggregation and/or lyosomal enzyme release in our test system. Release of biologically active amines from platelets exposed to insoluble complexes may be important in the initiation and propagation of inflammation in rheumatoid arthritis.